La Neuropedagogía Lúdica para mejorar la Comprensión Lectora en estudiantes de Cuarto grado paralelo B, de la Escuela de Educación General Básica Teniente Hugo Ortiz, Periodo 2020 – 2021 - Beltrán Alulima, Nathaly Maribel (2021)
The present Curricular Integration Work entitled: The Playful Neuropedagogy to improve Reading Compression in students of Fourth grade parallel B, of the Teniente Hugo Ortiz Basic General Education School, period 2020 - 2021, was a quantitative study, of a descriptive type, of quasi-experimental, and cross-sectional design; In addition, the scientific, deductive, inductive, analytical and synthetic methods were used, thus a survey was also applied to three teachers and the PROLEC-R Battery to the sample of seven students. The results of the survey applied to the teachers, 67% mention that they always apply strategies for the teaching-learning process of reading comprehension, while 33% almost always; The results of reading comprehension difficulties show a severe difficulty in: Reading of pseudowords 57% and Comprehension of sentences 100%, in the same way, it shows a level of difficulty in: Name of letters 86%, Equal-Different and Signs of score 57%, Reading of words and grammar structures 71%, Comprehension of texts 100%, whereas in oral comprehension 71% is in a normal average. It is concluded that the majority of teachers always use strategies such as videos, audios, reading texts, consulting words, for the teaching process - learning reading comprehension; In relation to reading comprehension, those investigated present difficulties at mild and severe levels (pretest), and after the intervention (posttest), as a whole they reach a normal average; Likewise, the improvement in Reading Comprehension is statistically verified, through the Wilcoxon Test that indicates: if the result is <0.05, the null hypothesis is rejected and the alternative hypothesis proposed as follows is approved: Playful Neuropedagogy improves Reading comprehension significantly in the population investigated. It is recommended that the educational institution provide spaces for the training of teachers on Play Neuropedagogy, in order to obtain better results not only in reading comprehension, as well as in academic performance.